2015
DOI: 10.1586/14787210.2015.1052793
|View full text |Cite
|
Sign up to set email alerts
|

The emerging threat of artemisinin resistance in malaria: focus on artemether-lumefantrine

Abstract: The development of artemisinin resistance in the Greater Mekong Subregion poses a significant threat to malaria elimination. Artemisinin-based combination therapies including artemether-lumefantrine (AL) are recommended by WHO as first-line treatment for uncomplicated Plasmodium falciparum malaria. This article provides a comprehensive review of the existing and latest data as a basis for interpretation of observed variability in parasite sensitivity to AL over the last 5 years. Clinical efficacy and preclinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 165 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…The resistance to AL is a growing debate [27, 28]; however this result should be considered with caution, knowing the absence of any biology test prior to anti-malarial use. This implies a possible use of anti-malarials outside the correct indication (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The resistance to AL is a growing debate [27, 28]; however this result should be considered with caution, knowing the absence of any biology test prior to anti-malarial use. This implies a possible use of anti-malarials outside the correct indication (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Among the Artemisinin-based combination therapies, artesunate-amodiaquine (ASAQ), artesunatesulfadoxine-pyrimethamine (ASSP), dihydroartemisinin-piperaquine (DHA/PPQ), artesunate-mefloquine (ASMQ) and AL are the most commonly recommended ACTs for the treatment of uncomplicated falciparum malaria in African countries [11]. Several recent studies have observed that these ACTs have maintained high efficacy (cure rate ≥ 95%) in many of these countries, despite their use for more than a decade [49][50][51]. Nevertheless, a study carried out in Angola from two different regions in 2013 and 2015 showed a lower efficacy (<90% cure rate) of AL.…”
Section: Discussionmentioning
confidence: 99%
“…days [32]. This leads to successive accumulation of the drug after the completion of the full dose su cient enough for the elimination of residual parasites and possibly prevention of new infection [32].…”
Section: Discussionmentioning
confidence: 99%